Estratégias metacognitivas de leitura e consolidação da memória de longo prazo - Fonseca, Gilda Maria Rodrigues (2006)
This research looks into the relationship between the processing and consolidation of information in theoretical and scientific texts by means of metacognitive strategies involved in the reading process. It was investigated whether academic students, when restructuring the information from a text through these strategies, would be assisted in the understanding of the text and in the consolidation of information in the long-term memory. We analysed, at first, the proficiency of both the intervention and control groups, as well as their reading strategy metacognitive awareness. Afterwards, the participants received intervention, involving explicit training in strategies (intervention group), or a similar set of instructions, but no explicit training (control group). After the examination, the intervention group showed significantly greater gains than the control group. According to the result, we confirm the initial hypothesis that the metacognitive strategies were able to promote the conscious control of the learning process, allowing the intervention group to understand and to retain more information from the studied text. These results demonstrate that it is possible to develop instructional activities which implement meaningful mnemonic strategies in the classroom, since they are procedures which also are responsible for comprehension.